Kontroversi Perzinahan di Mata Agama dan Hukum yang Berlaku di Indonesia dengan Fakta Lapangan - Desak Ayu Gangga Sitha Dewi (Universitas Islam Balitar, Blitar, 2020)
Adultery is a condition that occurs when two people who are not bound in a marriage or marriage bond or have intercourse or intercourse. This has actually become a public secret in society. There is, done by the majority, but still seen as a negative thing in society. Although commonplace, adultery itself is a disgrace to a community group, as much as possible they will cover it up. Every society's perspective looks at adultery from a different perspective. This research is intended to understand the concepts of adultery that are considered controversial from every side that is indeed influential in people's lives. Religion itself considers adultery as a great sin that must be avoided and as far as possible to be avoided, but in terms of community habits, this is something that is very common though always trying to cover up. Each country regulates adultery differently in its constitution. Indonesia as a country with a basis of eastern culture and godliness of the Almighty has its own arrangements regarding adultery in its laws. This arrangement is based on all the beliefs that have been held by the community for a long time. This matter will be discussed further in this paper using the literature review method.